The photography in the architectural journey: Margaret Michaelis and the GATEPAC. Greece and the URSS - López Rivera, Javier (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2013)
The search for the essence of places visited, has been a constant in many of the architects who started journeys, either of pleasure or of studies. This special attention to the place, as the example of famous Aalto’s journey to Spain in 1951, not was born after the second world war and not was exclusive of the architects of that period. Through the pictures of some journeys of GATEPAC’s East group, mainly takes from the reporter Margaret Michaelis and realized before spanish civil war, we observe that –at least the ‘modern’ catalans– claimed an architecture integrated into the landscape and therefore away from the Modern Movement postulates that, as we know, understood the place like a simple background where they must be cut architectures-objects.This article aims to analyze the role of photography in the journeys, through some examples of architects and photographers of modernity, who did not hesitate to rely on the power of images as carriers of the characteristic values of those landscapes traveled and on their facility of infinite reproduction as work material.